TELAAH MATEMATIS VARIASI LEBAR ARAH KIBLAT DI WILAYAH INDONESIA - Agung Laksana; Syarif, Muh Rasywan (ELFALAKY: Jurnal Ilmu Falak, 2022)
This study examines the mathematical study of variations in the width of the Qibla direction in the territory of Indonesia. Qibla direction measurement needs to be done properly through various tools and methods. Every measurement is always faced with uncertainty. The limited accuracy of measuring instruments is an important factor in determining whether or not a measurement is accurate. The vast territory of Indonesia has varying distances from the Kaaba, it should have different angular deviation limits. The research method is quantitative by taking the coordinates of 33 provinces throughout Indonesia as calculation material. This study aims to determine the variation in the width of the Qibla direction in Indonesia if the Qibla direction is limited by the coordinates of the forbidden land. The results showed that the angle of deviation of each province was different. The largest Qibla direction width is in Bengkulu province, which is 0° 19' 24.63". The smallest Qibla direction width is 0° 15' 2.09" in North Maluku province. This number is very small and ranges from human error. The boundary of the forbidden land as a reference for the Qibla direction needs to be reconsidered by considering various aspects.